Control and motivation in task performance of public servants at home office in the face of the COVID-19 pandemic (REGE Revista de Gestão, 2023)
Objective: To analyze the influence of output control, autonomous motivation, and controlled motivation on task performance of public servants at home office owing to the COVID-19 pandemic.Methodology: Survey research, based on the perception of 236 public servants; Structural Equation Modeling technique was used for data analysis.Results: Both autonomous motivation and output control are positively and significantly related to task performance.Research implications: The present study expands the literature with information about individual performance and management control, which can be related to the control, motivation and task performance of public servants at home office in a pandemic context.Practical implications: The results could offer a basis for understanding how managers can deal with the challenges while at home office. They can also provide managers with information that they can use to build management strategies to foster the performance of public servants at home office.Social implications: Home office can decrease commuting to a central workplace, alleviate traffic problems, and reduce car pollution. It also allows for business continuity in the face of storms and pandemics.Originality: Most studies about home office, COVID-19, and task performance have addressed personal, professional, and organizational characteristics. However, little is known about the analysis of combinations of the following constructs: output control, autonomous and controlled motivations, and how both affect task performance of public servants.